PERANCANGAN PILOT PLANT PENGOLAHAN AIR MINUM UNTUK ZONA PENDIDIKAN DAN RISET KAWASAN TECHNO PARK, KABUPATEN PELALAWAN - Hernaningsih, Taty (Jurnal Air Indonesia, 2015)
Techno Park regional development in order to increase regional competitiveness based on innovation and knowledge (konwledge based economy) requires infrastructure that can meet basic human needs, such as drinking water supply for the community. Techno Park region Pelalawan, Riau province located in the peat so that most of the water source is brownish and contains peat. While surface water sources such as rivers Kampar located far from the region. Therefore, to overcome the problems of water supply for the people who will live in the region need to be prepared water supply planning. Early stages of development is focused on the areas of education and research zone so that planning for water supply will also be prioritized in both these zones. Has calculated the drinking water needs based on projected population and water demand standard in these locations. Planning of water treatment plant will conduct in 5 stages yearly so that development is more economic with design capacity of 5 l / sec in 2033. Alternative sources of raw water are from Kampar river or groundwater that is used if transmission pipeline from the Kapuas river has not ben constructed. Technology of drinking water treatment with ultrafiltration processes that are environmentally friendly will be applied to meet the water needs of society. Transmission pipelines is planned of 15 inches diameter laying in parallel with lane highway from Kampar River ( location intake BPAB ) to the water treatment plant in the education zone . Keywords : Techno park region, water supply planning, ultrafiltrasi, peat area.